The Origin and Quality of the Groundwater of the Rawadanau Basin in Serang Banten, Indonesia (Rudarsko-geološko-naftni zbornik, 2021)
Rawadanau is a tropical mountain swamp located in Serang, Banten, Indonesia. Rawadanau groundwater is the main source of supply for the Cilegon Banten industrial area. Knowing the origin and quality of groundwater can help preserve existing resources. This paper aims to clarify the origin of Rawadanau groundwater with new evidence of stable isotopes (18O and 2H) and hydrochemical data. Field measurements include pH, temperature, EC, HCO3ˉ, while the analysis of cations, anions and stable isotopes were carried out in the laboratory. The existing water supplies include springs, excavated wells, and river water. Cluster hierarchy analysis based on water chemistry and stable isotopes can be grouped into two, cluster K (K1 and K2) and cluster L. Data δ18O and δ2H springs in Rawadanau indicate that they are of meteoric origin and that there has been evaporation from several springs. Water comes from meteoric water with a stable isotope content of δ18O between -6.39 to -4.82 ‰ and δ2H between -41.35 to -31.30 ‰, which are controlled by two main mechanisms, namely rock dissolution, and evaporation dominance. Aquifers are composed of volcanic rocks with a dominant composition of porphyritic andesite, basaltic andesite, and andesite. According to the multivariate statistical analysis result other than pH and SO42-, all parameters (cations and anions) showed a significant correlation. There are four facies of groundwater, namely Ca-HCO3, Ca-Mg-HCO3, Mg-Ca-HCO3, and Na-Cl.